2021
DOI: 10.1101/2021.12.14.21267615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of COVID-19 vaccines against the Omicron (B.1.1.529) variant of concern

Abstract: Background A rapid increase in cases due to the SARS-CoV-2 Omicron (B.1.1.529) variant in highly vaccinated populations has raised concerns about the effectiveness of current vaccines. Methods We used a test-negative case-control design to estimate vaccine effectiveness (VE) against symptomatic disease caused by the Omicron and Delta variants in England. VE was calculated after primary immunisation with two BNT162b2 or ChAdOx1 doses, and at 2+ weeks following a BNT162b2 booster. Results Between 27 November an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
291
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(323 citation statements)
references
References 22 publications
27
291
1
4
Order By: Relevance
“…However, the good news is that after two doses of inactivated vaccines as the “priming” shot, a third homologous inactivated vaccine booster or a heterologous protein subunit vaccine booster could elevate neutralization titer against Omicron. Our results are quite comparable to studies on the same inactivated vaccine 23 or other vaccines 25 , and again supported by the real-world data showing a third dose booster vaccination provides increased protection against Omicron 26 .…”
Section: Discussionsupporting
confidence: 88%
“…However, the good news is that after two doses of inactivated vaccines as the “priming” shot, a third homologous inactivated vaccine booster or a heterologous protein subunit vaccine booster could elevate neutralization titer against Omicron. Our results are quite comparable to studies on the same inactivated vaccine 23 or other vaccines 25 , and again supported by the real-world data showing a third dose booster vaccination provides increased protection against Omicron 26 .…”
Section: Discussionsupporting
confidence: 88%
“…However, the clinical relevance of such B mem cell reactivity during protective immunity in humans remains unknown. We demonstrated that the majority of human B mem cells elicited by two doses of mRNA vaccine are able to capture SARS-CoV-2 variants, despite the striking resistance of the variants to pre-existing antibodies ( 1214, 16, 17 ). Moreover, such memory cross-reactivity was linked to the cross-neutralizing activities against the variants including highly mutated Omicron variant.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the Omicron variant drastically reduced the neutralizing activity of circulating antibodies in fully vaccinated individuals and many therapeutic monoclonal antibodies in clinical use ( 1216 ). Epidemiological evidence further suggest a reduction in the vaccine effectiveness against this variant ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with emerging clinical data on the Omicron variant demonstrating higher rates of reinfection 11 and vaccine breakthroughs. In fact, recent reports showed that the efficacy of two doses of BNT162b2 vaccine has dropped from over 90% against the original SARS-CoV-2 strain to approximately 40% and 33% against B.1.1.529 in the United Kingdom 32 and South Africa 33 , respectively. Even a third booster shot may not adequately protect against Omicron infection 32,34 , but of course it is advisable to do so.…”
Section: Discussionmentioning
confidence: 99%